Upaya Penanganan Overcrowding Berdasarkan Undang-Undang Nomor 1 Tahun 2023 - Belvina Azahra; Karina Salsabilla; Maulana Sena Al Jabbar; Muhammad Makin; Ria Anggraeni Utami (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
The phenomenon of overcrowding in correctional institutions has reached a critical point, threatening the stability of the criminal justice system in Indonesia. This study aims to analyze how Law No. 1 of  2023 concerning the Criminal Code (National Criminal Code) addresses this problem through criminal policy reform. Using normative legal research methods, this study examines new de-incarceration norms in the National Criminal Code. The study concludes that efforts to address overcrowding in Law No. 1 of 2023 are carried out through modifications to more humane sanctions, namely prioritizing non prison sentences (community work and supervision) for crimes punishable by imprisonment under five years. Furthermore, expanding the requirements for conditional sentences and formally recognizing restorative justice are expected to minimize the influx of convicts into prisons. The effectiveness of these instruments requires synchronization between law enforcement agencies and the availability of monitoring infrastructure outside prisons. The National Criminal Code offers new hope for resolving the issue of overcrowding through a criminalization approach that is no longer prison centric.